Oxidation Stability of Nanographite Materials. Issue 9 (21st May 2013) - Li, Huaiguang; Cheng, Niancai; Zheng, Yao; Zhang, Xiao; Lv, Haifeng; He, Daping; Pan, Mu; Kleitz, Freddy; Qiao, Shi Zhang; Mu, Shichun
<x xml:space="preserve">Abstract</x> The oxidation stabilities of nanographite materials (NGMs) including single/double‐walled carbon nanotubes and graphene are investigated. The key factors that influence the oxidation behavior of NGMs such as double layer capacitance, electrical conductivity, and specific surface area is clarified. A facile and effective solution to increase resistance to oxidation is developed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>